Exploring the leishmanicidal potential of terpenoids: a comprehensive review on mechanisms of cell death - Rodrigues, Ana Carolina Jacob; Carloto, Amanda Cristina Machado; Gonçalves, Manoela Daiele; Concato, Virgínia Márcia; Detoni, Mariana Barbosa; Santos, Yasmin Munhoz dos; Cruz, Ellen Mayara Souza; Madureira, Maria Beatriz; Nunes, Angélica Paulina; Pires, Maria Fernanda Maya Kuriki; Santos, Natália Concimo; Marques, Rafaela Evangelista dos Santos; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmaniasis is a neglected tropical disease with a wide spectrum of clinical manifestations, ranging from visceral to cutaneous, with millions of new cases and thousands of deaths reported each year. The species of Leishmania and the immune response of the host determine the severity of the disease. Leishmaniasis remains challenging to diagnose and treat, and there is no vaccine available. Several studies have been conducted on the use of herbal medicines for the treatment of leishmaniasis. Natural products can provide an inexhaustible source of chemical diversity with therapeutic potential. Terpenes are a class of natural products derived from a single isoprene unit, a five-carbon compound that forms the basic structure of isoprenoids. This review focuses on the most important and recent advances in the treatment of parasites of the genus Leishmania with different subclasses of terpenes. Several mechanisms have been proposed in the literature, including increased oxidative stress, immunomodulatory role, and induction of different types of parasite cell death. However, this information needs to be brought together to provide an overview of how these compounds can be used as therapeutic tools for drug development and as a successful adjuvant strategy against Leishmania sp.